A review on pulsating heat pipes: From solar to cryogenic applications. (15th July 2018) - Alhuyi Nazari, Mohammad; Ahmadi, Mohammad H.; Ghasempour, Roghayeh; Shafii, Mohammad Behshad; Mahian, Omid; Kalogirou, Soteris; Wongwises, Somchai
Highlights: Pulsating heat pipes (PHPs) are compact cooling equipment used for various applications. PHP can be used in renewable energy systems, cooling electronic devices, heat recovery systems. Various applications of PHPs are reviewed and analyzed. PHPs are efficient and reliable devices for utilization in various energy systems. Abstract: Pulsating heat pipes (PHPs) are compact cooling equipment used for various applications. This type of heat pipes can be used in renewable energy systems, cooling electronic devices, heat recovery systems and many other applications. Since PHPs have superior thermal performance, by applying them in energy systems enhance their efficiency. In addition, PHPs are a reliable medium for cooling various devices which have high heat flux. In this study, various works conducted on the applications of PHPs are reviewed and analyzed. It is concluded that PHPs are efficient and reliable devices for utilization in various energy systems. Moreover, at very low temperatures, such as cryogenic applications, they can transfer heat efficiently. For instance, by applying cryogenic PHP it is possible to achieve up to 12, 000 W/m K which is much higher than metal thermal conductivity at those temperatures.